The Effect of Return on Equity and Inventory Turnover on Firm Value Moderated by Current Ratio: A Study on the Transportation and Logistics Sector in Indonesia - A, Puti Indah Balqis; Janurika, Renita; Sianturi, Rolas Tarida; Gantino, Rilla (SAFE-Network, 2026)
This study aims to analyze the effect of Return on Equity (ROE) and Inventory Turnover (ITO) on firm value as measured by Price to Book Value (PBV), as well as to examine the moderating role of the Current Ratio (CR) in companies within the transportation and logistics sector listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach using panel data regression on 110 observations obtained through purposive sampling. Secondary data from annual financial statements were analyzed using the Common Effect Model with robust standard errors. The results indicate that ROE does not have a significant effect on PBV, while Inventory Turnover and Current Ratio have a negative and significant effect on PBV. Moderation analysis reveals that the Current Ratio does not moderate the relationship between ROE and PBV but strengthens the effect of Inventory Turnover on PBV. These findings suggest that market responses to financial performance are contextual and influenced by the balance between operational efficiency and corporate liquidity, implying that firm value should not be assessed based on a single financial ratio but through the interaction of multiple financial performance indicators.